PROPOSED INTEGRATED MARKETING COMMUNICATION STRATEGY TO RAISE BRAND AWARENESS FOR PAVETTIA SKIN CARE - Nabila, Valisha; Wibowo, Satya Aditya (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
Pavettia is a natural skincare brand in Indonesia that use natural ingredients. The average number of Pavettia’s products sold per month only reached 143 products while their competitors successfully sold thousands of products. The brand awareness of Pavettia is considered low. According to the research, 94% of 100 respondents never heard about Pavettia brand. This research was conducted to identify the problems faced by Pavettia Skin Care and proposed solutions to raise their brand awareness. In this research, both qualitative and quantitative methods are used. In-depth interviews with Pavettia’s internal management was conducted and online questionnaires were distributed to 164 respondents which are the target market of Pavettia. The secondary data were gathered from Pavettia’s internal data and other sources such as textbooks, journals, and others. The STP Analysis and Marketing Mix (4Ps) were conducted to propose Integrated Marketing Communication Strategy for Pavettia. It can be concluded that Pavettia has a huge potential as a local natural skin care brand in Indonesia. However, they need to do several integrated marketing strategy.